2010
DOI: 10.1111/j.1365-2621.2010.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of the milk whey products obtained by enzymatic and microbial hydrolysis

Abstract: The objective of this study was to investigate the in vitro immunomodulatory effect of milk whey through enzymatic hydrolysis, microbial fermentation and two-stage hydrolytic reactions (enzymatic and microbial reactions) by analysing cytokine profiles. Results indicated that the milk whey sample fermented by Lactobacillus kefiranofaciens M1 and two-stage hydrolytic reactions (hydrolysed by Alcalase and then fermented by L. kefiranofaciens M1) could significantly induce the production of tumour necrosis factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
2
11
0
3
Order By: Relevance
“…Huang et al . () reported that milk whey hydrolysed by alcalase shows significantly higher level ( P < 0.05) than that hydrolysed by neutrase and pepsin in production of TNF‐α and IL‐12. Shark protein hydrolysate (prepared by trypsin–chymotrypsin) stimulated higher level of IL‐6 than that produced by unhydrolysed fish proteins, but lower than that produced by LPS (Mallet et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Huang et al . () reported that milk whey hydrolysed by alcalase shows significantly higher level ( P < 0.05) than that hydrolysed by neutrase and pepsin in production of TNF‐α and IL‐12. Shark protein hydrolysate (prepared by trypsin–chymotrypsin) stimulated higher level of IL‐6 than that produced by unhydrolysed fish proteins, but lower than that produced by LPS (Mallet et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Some researchers reported that the immunomodulatory peptides could replace immunomodulatory pharmaceutical for preventing and controlling the chronic diseases (Hou et al ., ). The reported immunomodulatory peptides from food proteins include whey (Huang et al ., ; Rodríguez‐Carrio et al ., ), egg white (Lozano‐Ojalvo et al ., ), hazelnut (Ren et al ., ), casein (O'Sullivan et al ., ) and fish (Hou et al ., ). When compared to the peptides mentioned above, wheat germ is less expensive and is an attractive potential resource to make immunomodulatory peptides.…”
Section: Introductionmentioning
confidence: 99%
“…21,50) It was reported that WPC itself induces TNF-α production in RAW cells and murine splenocytes. 51) These results suggest that the Maillard reaction may contribute to induction of the above cytokines produced by macrophages against pathogenic bacteria in the gut mucosa.…”
Section: Effects Of G-wpc On No Production and Pro-inflammatory Cytokmentioning
confidence: 99%
“…stomach conditions (29,30)), and the resulting released peptides were analyzed for function. Through this approach, dozens of protein fragments, mostly from bovine milk, but also from human milk, have been shown to have different functions (31), including antimicrobial (32,33), antihypertensive (34,35), immunomodulatory (36,37), and opioid-like (38) actions. However, such in vitro digestion approaches fail to reveal the peptide content present endogenously in milk.…”
mentioning
confidence: 99%